MAC scheduling using channel state diversity for high-throughput IEEE 802.11 mesh networks. - Jian Zhang; Chen, Peter; Marsic, Ivan.
The head-of-line blocking problem impairs the throughput of the hotspot nodes in multihop wireless mesh networks. FIFO scheduling in the current IEEE 802.11 MAC suffers from this problem when the network is highly loaded. The problem may keep the sender in backoff stage up to 70 percent of the time, leading to significant throughput degradation. One solution is to increase the RTS success rate by extending the RTS frame to multicast RTS so that multiple receivers can be checked simultaneously. We present an adaptive learning process that constructs the receiver list based on the dynamic channel-state diversity of candidate receivers. Our variable-length channel-state-based scheduling scheme outperforms the basic MRTS by 20-60 percent.
Keywords: FIFO scheduling; IEEE 802.11 mesh networks; MAC scheduling; Adaptive learning process; Channel diversity; Head-of-line blocking; High-throughput mesh network; Multihop wireless mesh network